Joining Technologies for Composites and Dissimilar Materials, Volume 10 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Cloud, Gary L.; Patterson, Eann.; Backman, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Joining Technologies for Composites and Dissimilar Materials, Volume 10 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the tenth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Composite Joints Non-Adhesive Bonding Adhesive Bonding Joining of Ceramic & Other Materials.
1 How To Join Fiber Reinforced Composite Parts An Experimental Investigation -- 2 Analysis of a Composite Pi/T joint using an FE Model and DIC -- 3 5xxx Aluminum Sensitization and Application of Laminated Composite Patch Repairs -- 4 Investigation and Improvement of Composite T joints with Metallic Arrow pin Reinforcement -- 5 Review of Natural Joints and Bio inspired CFRP to Steel Joints -- 6 Fabrication of 3D Thermoplastic Sandwich Structures Utilizing Ultrasonic Spot Welding -- 7 Impact and Lap Shear Properties of Ultrasonically Spot Welded Composite Lap Joints -- 8 Numerical and Experimental Characterization of Hybrid Fastening System in Composite Joints -- 9 Application of Digital Image Correlation to the Thick Adherend Shear Test -- 10 Interfacial Strength of Thin Film Measurement by Laser Spallation -- 11 Joining of UHTC Composites Using Metallic Interlayer -- 12 Metal to Composite Structural Joining for Drivetrain Applications -- 13 Short term Preload Relaxation in Composite Bolted Joints Monitored with Reusable Optical Sensors.
Keywords: Mechanics, Applied; Solids; Ceramic materials; Building construction; Solid Mechanics; Ceramics; Solid Construction